Экономичный метод приближенной минимизации ДНФ булевых функций - Luzin, S. Yu.; Polubasov, O. B. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Within the tasks of VLSI design and from the standpoint of solution optimality, a method for minimizing Boolean functions is proposed, based on the parallel growth of intervals forming the solution. The method includes a procedure for systematic correction of the solution and makes it possible to minimize Boolean functions given either in the form of perfect DNF or as a set of ternary vectors.